2021
DOI: 10.1089/dia.2020.0631
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Metrics: Need for Development of Consensus Standards for Reporting of Insulin Dosing Data

Abstract: The advent of connected insulin pens will generate an avalanche of digital insulin data, especially in the context of prandial-and multiple daily injection-insulin regimens. There is a need for the diabetes community to develop standards for such data, analogous to what has been achieved using the ambulatory glucose profile and associated metrics for glucose, permitting harmonization of data reporting for multiple devices and facilitating integration of glucose, insulin, food intake, and physical activity data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Depending on the use, each of the reviewed solutions has some peculiarities that can be exploited while performing CGM data analysis. It has to be noted that the Tidepool platform presents also some additional services since it enables the patient to integrate data from all his/her devices (such as not only CGM but also insulin pumps, blood meters and ketone meters) in a single app, sharing them directly with the doctor and for this reason representing a powerful solution for telemedicine practice; however, this will rise the need of standardization of metrics related to insulin, as proposed in a very recent study 75 . Moreover, the consistent data collection could be of interest for researchers who apply for the Tidepool Clinical Study Platform, where one will have access to de-identified patient data.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the use, each of the reviewed solutions has some peculiarities that can be exploited while performing CGM data analysis. It has to be noted that the Tidepool platform presents also some additional services since it enables the patient to integrate data from all his/her devices (such as not only CGM but also insulin pumps, blood meters and ketone meters) in a single app, sharing them directly with the doctor and for this reason representing a powerful solution for telemedicine practice; however, this will rise the need of standardization of metrics related to insulin, as proposed in a very recent study 75 . Moreover, the consistent data collection could be of interest for researchers who apply for the Tidepool Clinical Study Platform, where one will have access to de-identified patient data.…”
Section: Discussionmentioning
confidence: 99%
“…One benefit of connected systems are their ability to support telehealth and population health management; this is particularly relevant given the coronavirus disease 2019 (COVID-19) pandemic ( 20 23 ). Although there is increasing discussion regarding the likely future importance of connected insulin pen systems and the need for standards for data integration ( 10 , 23 ), there is currently a paucity of published clinical data ( 24 27 ). Therefore, although relatively small, this study is an important contribution to the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this could lead to failure to identify clinical problems and result in less than optimal clinical decision making. Once the content for presentation has been selected, there are numerous factors to be optimized: definitions and terminology, choice of metrics, 38,58,59 methods for display (tables, charts, graphs, and text), color coding, size and shape of panels, and methods to identify or ''flag'' anomalous, discordant, or worrisome findings.…”
Section: Discussionmentioning
confidence: 99%
“…24,[29][30][31][32][33][34] Patients periodically change the make and models of their devices, and periodic software updates are likely to drive further increases in the number of reports and reporting systems. Thus, there is an urgent need for standardization of the metrics and reports of these diabetes technology devices, 38,39 as in the case of previous forms of diabetes technology. [40][41][42][43][44][45] Although there will always be some variability in reports as developers seek to improve and optimize their systems, we expect that it should be possible to standardize at least a core section of the reports forming a one-page summary or ''dashboard.''…”
Section: Introductionmentioning
confidence: 99%